On the Sources of Nihilism in Dostoevsky's "Crime and Punishment" - Galounis, Markos (RUS (São Paulo), 2020)
It is well known that Dostoevsky's Crime and Punishment reflects the intellectual milieu of the period of its conception. More specifically, the motivation of Raskolnikov's crime is rooted in the nihilism of the radical intelligentsia of the period. In this article, the ideology of Raskolnikov is identified with the ideology of the representatives of the radical intelligentsia, namely Nikolai Chernyshevsky and Dimitri Pisarev. It also traces the continuity and discontinuity of the ideas of these thinkers. Finally, argues that Dostoevsky perceived the evolution and radicalization of the intelligentsia's ideas through the lenses of the evolution and radicalization of the Left Hegelians, namely Feuerbach and Stirner, whose ideology influenced the Russian radical intelligentsia. Thus is brought to the fore the intellectual origins of the Russian radical intelligentsia's nihilism, which was seminal to Dostoevsky's Crime and Punishment.